Научно-библиографическая работа вузовских библиотек Литовской ССР (1958–1975 г.) - Юрчюконене, Аполония; Пятраускене, Зофия Мильда (Knygotyra, 1981)
The libraries of the Lithuanian higher schools make some contribution to the bibliographic activities of Lithuanian scientific libraries. They take an active part of the study of local lore. They contribute to the preparation of a periodical “Yearbook of the Soviet Lithuanica” and Lithuanian retrospective analitical bibliography which is going to be published.The higher school libraries prepare and publish lists of recommended literature if they are required according to the school curriculum and student educational programmes. Science indices are made in accordance to the higher school research work objectives. Subject indices, repertories, personalias, collection invertories are published and not only included into the system of bibliographic publications but sometimes they appear to be the first case of bibliographic description of some topics.One of the basic tasks of the bibliographic work is the accumulation of the higher school history material. But the shortage of methodic guidance and documents classification system is felt here. The question concerning bibliography of the higher school teachers publications is not solved also. Some of the schools issue publication indices following the recommendations, others keep the material in files. But huge files are not only subject to time tests but the searching time is reduced as well.